EXPLORING CULTURAL UNDERSTANDING IN ENGLISH LANGUAGE TEACHING (ELT) - Maratul Azizah; Nanang Jayani; Nilla Rojana (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
The research of this study to explore and give a clear explanation and develop culture integrated EFL teaching learning classroom platform and curriculum for effective communication and understanding cross cultural from perspective of the teachers. This research was carried out through qualitative research with a case study design. This research used purposive sampling which is all English teachers (two English teacher in total) in SMK Ashiddiqiyah are four teachers. The instruments used in this research were observation and interviews. The data were collected by conducting semi-structured interviews with English teachers. The results of this research show that the English teachers recognize the significance of cultural understanding in EFL. They also face various challenges and use similar methods and materials to integrate culture into their classroom. The findings from this research highlighted EFL teachers can overcome challenges and integrate cultural understanding into their teaching by embracing resourcefulness and creativity. It's hoped that this research can provide views to English teachers and education practitioners in foster rich learning experiences that equip students to navigate the interconnected world with confidence and intercultural competence.   ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi dan memberikan penjelasan yang jelas serta mengembangkan platform dan kurikulum pembelajaran EFL (English as a Foreign Language) yang terintegrasi budaya untuk komunikasi dan pemahaman lintas budaya yang efektif dari perspektif guru. Penelitian ini dilakukan melalui penelitian kualitatif dengan desain studi kasus. Penelitian ini menggunakan purposive sampling yaitu seluruh guru Bahasa Inggris (dua guru Bahasa Inggris) di SMK Ashiddiqiyah berjumlah empat guru. Instrumen yang digunakan dalam penelitian ini adalah observasi dan wawancara. Data dikumpulkan dengan melakukan wawancara semi-terstruktur dengan guru Bahasa Inggris. Hasil penelitian ini menunjukkan bahwa guru Bahasa Inggris menyadari pentingnya pemahaman budaya dalam EFL. Mereka juga menghadapi berbagai tantangan dan menggunakan metode dan materi yang serupa untuk mengintegrasikan budaya ke dalam kelas mereka. Temuan dari penelitian ini menyoroti bahwa guru EFL dapat mengatasi tantangan dan mengintegrasikan pemahaman budaya ke dalam pengajaran mereka dengan merangkul daya cipta dan kreativitas. Diharapkan penelitian ini dapat memberikan pandangan kepada guru Bahasa Inggris dan praktisi pendidikan dalam menumbuhkan pengalaman belajar yang kaya yang membekali siswa untuk menavigasi dunia yang saling terhubung dengan percaya diri dan kompetensi antarbudaya.